Compare the effect of eight weeks aerobic and resistance training on Oxidant, antioxidant status and lipid profile in obese girls - Mozhgan Ahmadi; Asieh Abbassi Daloii; Saeedeh Shadmehri; Neda Agghaei Bahmanbeglu (Shahid Beheshti University, 2018)
Purpose: The aim of this study was to compare the effect of eight weeks aerobic and resistance training onoxidant, antioxidant status and lipid profile in obese girlsMethods: Thirty obese girls (age 30±5years, height 1.60±2m, weight 85.23±6.7kg, Body mass index 31-33kg/m2) were divided randomly into three aerobic exercise, resistance and control groups. Experimentalgroups of aerobic exercise performed on a treadmill by 60 to 75% of heart rate reserve and intensityresistance training 55 to 75% 1RM for 8 weeks. Blood samples of the subjects before and after 48 hours oftraining and 12 hours of fasting protocols were collected. Data analysis using ANOVA and Tukey post hoc testwas conducted at P≤0.05.Results: Aerobic training significantly reduced the level of malondialdehyde and significantly increasedsuperoxide dismutase and total antioxidant capacity of plasma in obese girls (P≤0.05). However, there wasno difference between the effect of eight weeks aerobic and resistance training in plasma nitric oxide, inobese girls (P=0.069).Conclusions: It seems aerobic training can make significant changes in the body oxidative and anti-oxidativeand adjusting lipid profile, reduce risk of cardiovascular disease in people with obesity .